HABITUAL HEALTH ENHANCING PHYSICAL ACTIVITY IS RELATED TO LOWER LEVELS OF BODY ADIPOSITY AND BLOOD PRESSURE AMONG COMMUNITY DWELLING ADULTS IN MAIDUGURI, NIGERIA - Oyeyemi AL; Masta AM; Rufai AA; Maduagwu SM; Saidu IA; Oyeyemi AY (Ntec Specialist, 2018)
Community-based promotion of physical activity for health and primary prevention of chronic non-communicable diseases are integral components of physiotherapy practice. This study examined the relationship between habitual health enhancing physical activity and cardiometabolic risk factors among community dwelling adults in Maiduguri, Nigeria. Methodology: A cross-sectional survey of 280 male and female adults (age=20-76 years) randomly selected from the State Low Cost Housing Estate in Maiduguri. Participants' physical activity was measured using the international physical activity questionnaire-short form. Health enhancing physical activity was defined as ≥ 150 minutes/week of moderate to vigorous physical activity (MVPA). Blood pressure, body weight, height, and waist and hip circumferences were measured following standardized procedures. Results: Most of the participants (85%) engaged in sufficient health enhancing MVPA. The prevalence of generalized obesity (26.1%) and overweight (36.2%), central obesity (68.6%), and hypertension (26.4%) was relatively high. Overall, there were significant negative associations between MVPA and BMI (β = -0.163, P= 0.005), and waist-to-hip ratio (β = -0.138, P= 0.023). Both BMI and waist-to-hip ratio accounted for about 5% (R2 =0.049) of the variance in MVPA. In gender specific analysis, only among women was MVPA significantly associated with lower BMI (β = -0.189, P= 0.046), and decreased systolic blood pressure (β = -0.241, P= 0.010) and diastolic blood pressure (β = -0.212, P= 0.026). Conclusions: Higher health enhancing MVPA was associated with lower levels of obesity and blood pressure among community dwelling adults (especially women). This evidence can be used to inform effective community physiotherapy practice and health promotion in Maiduguri